EFEITOS DA CALAGEM E FERTILIZAÇÃO SOBRE A ANATOMIA DE RAIZ DA ERVA-MATE (Ilex paraguariensis A. ST. Hil.) - COELHO, GERALDO C.; LIBARDONI, JULIANA B.; FERNANDES, SANDRA B. V. (Salão do Conhecimento, 2013)
Resumo